Is 2 h of Hypothermic Machine Perfusion for Pancreas Preservation Effective in Improving Graft Reperfusion? - Benoit Mesnard, MD; Christophe Masset, MD, PhD; Etohan Ogbemudia, MD, PhD; Sarah Bruneau, PhD; Mohamed Elzawahry, MD; Stéphanie Le Bas-Bernardet, PhD; David Minault; Jeremy Hervouet; Diego Cantarovich, MD, PhD; Jérôme Rigaud, MD, PhD; Lionel Badet, MD, PhD; Peter Friend, MD, PhD; et al. (Transplantation Direct)
Background. Static cold storage (SCS) remains the standard method for organ preservation. The development of parenchymal edema during prolonged hypothermic machine perfusion (HMP) was a major barrier to the introduction of this technique for the preservation of pancreases. A short period of HMP could optimize the pancreas for reperfusion while minimizing the side effects related to perfusion. Our objective is to evaluate the impact of short-term HMP on the pancreatic reperfusion. Methods. A preclinical study using a controlled donation after circulatory death porcine model was conducted. After procurement, the pancreases were preserved under hypothermic conditions for 2 h either by SCS (n = 4) or HMP (n = 4). After these 2 h of preservation, the pancreases were reperfused using a normothermic machine perfusion (NMP) for 2 h. During NMP, oxygenation, perfusion parameters, biochemical analyses, a glucose stimulation insulin secretion test, and an evaluation of ischemia/reperfusion injury by photoacoustic tomography were assessed. Results. During NMP, resistance indices were significantly lower in the HMP group compared with the SCS group, even after 2 h of reperfusion. The tissue oxygen partial pressure was higher throughout NMP after HMP preservation. Lactate and amylase levels were equal between the 2 groups. Lipase levels were higher in the HMP group. The glucose stimulation test showed no difference between the 2 groups. Photoacoustic tomography assessment showed no endothelial damage in either group. Conclusions. Our study suggests that a short-term HMP applied to pancreases for 2 h is effective in reducing resistance indexes and improving oxygenation.